Formation of PEO coatings on binary material Mg-33wt%Ti processed by high energy ball milling (HEBM) (2022)
ABSTRACT: The manufacture of light alloys has caused a significant impact in the world of additive manufacturing. Among the highly attractive light metals in the aeronautical, automotive, and biomaterials industries are titanium and magnesium, which, due to their low density and high strength-to-weight ratio, have been seen as having great potential for application in these areas. Magnesium alloys are of growing interest in many industrial fields, and their properties are being improved and their performance increased; however, their use is still restricted due to their moderate mechanical strength and high reactivity, the latter of which reduces their corrosion resistance in different media, limiting their application in many desirable applications. Titanium alloys, on the other hand, offer excellent properties, both mechanical and chemical stability, but have a density approximately 2.6 times that of magnesium. In order to increase the mechanical properties and corrosion resistance of magnesium, as well as to decrease the density of titanium, Mg-33wt%Ti binary material were successfully synthesized by high energy ball milling (HEBM), sintered via hot isostatic pressure (HIP), and then surface modified by plasma electrolytic oxidation (PEO) in phosphate-based electrolyte for corrosion protection. This study focused on two aspects: (i) the processing conditions to obtain the substrate and (ii) the effect of electrolytic plasma oxidation of its surface on the corrosion resistance. For these purposes, scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy were employed. The corrosion resistance of the coated material was evaluated by electrochemical impedance spectroscopy in a 0.01M sulfate solution. It was found that the surface modification of the binary Mg-Ti material improved the corrosion resistance of the substrate.